Global DNA methylation of WTC prostate cancer tissues show signature differences compared to non-exposed cases. (3rd March 2022) - Yu, Haocheng; Tuminello, Stephanie; Alpert, Naomi; van Gerwen, Maaike; Yoo, Seungyeul; Mulholland, David J; Aaronson, Stuart A; Donovan, Michael; Oh, William K; Gong, Yixuan; Wang, Li; Zhu, Jun; et al.
Abstract: There is increased incidence of prostate cancer (PC) among World Trade Center (WTC)-exposed responders and community members, with preliminary evidence suggestive of more aggressive disease. While previous research is supportive of differences in DNA methylation and gene expression as a consequence of WTC exposure, as measured in blood of healthy individuals, the epigenetics of WTC PC tissues has yet to be explored. Patients were recruited from the World Trade Center Health Program. Non-WTC PC samples were frequency matched on age, race/ethnicity and Gleason score. Bisulfite-treated DNA was extracted from tumor tissue blocks and used to assess global DNA methylation with the MethylationEPIC BeadChip. Differential and pathway enrichment analyses were conducted. RNA from the same tumor blocks was used for gene expression analysis to further support DNA methylation findings. Methylation data were generated for 28 samples (13 WTC and 15 non-WTC). Statistically significant differences in methylation were observed for 3, 586 genes; on average WTC samples were statistically significantly more hypermethylated ( P = 0.04131). Pathway enrichment analysis revealed hypermethylation in epithelial mesenchymal transition (EMT), hypoxia, mitotic spindle, TNFA signaling via NFKB, WNT signaling, and TGF beta signaling pathways in WTC compared to non-WTC samples. The androgen response, G2M and MYC target pathways were hypomethylated. These results correlated well with RNA gene expression. In conclusion, long-term epigenic changes associated with WTC dust exposure were observed in PC tissues. These occurred in genes of critical pathways, likely increasing prostate tumorigenesis potential. This warrants analysis of larger WTC groups and other cancer types. Abstract : There is increased incidence of prostate cancer among World Trade Center exposed persons. WTC exposure may be acting on prostate tumorigenesis through epigenetic mechanisms. Identifying which genes are dysregulated could have implications for cancer-screening and treatment within this high-risk group. Graphical Abstract: